2014
DOI: 10.1016/j.breast.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Is breast cancer from Sub Saharan Africa truly receptor poor? Prevalence of ER/PR/HER2 in breast cancer from Kenya

Abstract: We present a definitive prospective analysis of ER/PR/HER2 from a single center and demonstrate that prevalence of receptor status from SSA is comparable with that in the West.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
53
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 13 publications
8
53
3
Order By: Relevance
“…Nearly half of cases had high-grade tumours and over 80% of those with available lymph node information had lymph node involvement. One potential explanation for this may be that women with more aggressive tumours seek care and receive diagnostic services compared to women with slower progressing tumours 4 . A majority of cases occurred in women under 50 years of age, and the mean age was 48.6 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nearly half of cases had high-grade tumours and over 80% of those with available lymph node information had lymph node involvement. One potential explanation for this may be that women with more aggressive tumours seek care and receive diagnostic services compared to women with slower progressing tumours 4 . A majority of cases occurred in women under 50 years of age, and the mean age was 48.6 years.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the absence of HR status testing in most African settings is a major deficiency in care that requires correction, not only in Malawi but throughout the region. HR positivity varies widely across Africa, 4,12,13 and routine testing would ensure that women with HR-negative cancers are spared ineffective hormonal therapy. It would also identify many women who would benefit from tamoxifen, which is relatively inexpensive, well-tolerated, and available in Malawi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to point out that although most of the studies have attributed a high incidence of TNBC in African women [van Bogaert et al, 2013;Yarney et al, 2008;Ly et al, 2012;McCormack et al, 2013;Galukande et al, 2014], some have reported that hormone receptor-negative cases can be overestimated, due, as mentioned above, to technical difficulties encountered by pathologists in low-income countries in tissue handling and hormone receptors IHC evaluation and scoring [Anderson et al, 2006;AkaroloAntony et al, 2010]. Therefore, the accurate percentage of cases in Sub-Saharan Africa that are hormone receptor negative remains unclear, with highly variable data ranging from 30-75% [Huo et al, 2009;Sayed et al, 2014]. This wide variability of both hormone receptors and ERBB2 status has a direct impact on patient treatment in South Africa where the selection of patients to immune and/or endocrine therapy could be inappropriately based [Akarolo-Antony et al, 2010;Galukande et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor size, tumor grade, presence of lympho-vascular invasion, lymph node metastases and extra nodal extension were documented. ER/PR/HER2 status was analyzed on the Dako Automated platform as previously reported,[10] and tumors were assigned into 3 major breast cancer molecular subtypes based on immunohistochemistry: ER and/or PR positive and HER2 positive or negative (Luminal A/B), ER/PR negative and HER2 positive (HER2 enriched), and ER/PR and HER2 negative (Triple Negative).…”
Section: Methodsmentioning
confidence: 99%